IDENTIFIKASI KESULITAN GURU PKn SMA di WILAYAH KECAMATAN SAWAHAN KOTA SURABAYA DALAM MENGIMPLEMENTASIKAN STRATEGI PEMBELAJARAN INOVATIF - Suhartono, Suhartono PPKn (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Citizenship or Civics Education is a subject that is expected to shape the attitude and character of students. Learning activities in the classroom is not always fun. Teachers have difficulty in delivery of civic education materials to students. Civics teachers in the delivery of materials more commonly used conventional methods that lecture. As a result, the use of such methods only position students to be quiet, listen, take notes, and memorize. So with the policy of the use of innovative teaching strategies in the delivery of civic education materials are expected to assist students in understanding the material. Various types of innovative learning strategis such as Quantum Learning Strategies, Learning Strategies Inquiry, Problem Based Learning Strategies, Cooperative Learning Strategies, Contextual Learning Strategies, and Active Learning Strategies to provide facilities or provide a solution to the difficulties of the teacher in the classroom when the delivery of material.Methods of data collection in this thesis is that the questionnaire method is the main method in the research and documentation methods are used as a method to support in this study. Research is Education Departmen Sawahan. The data analysis technique used is descriptive statistical analysis techniques with the percentage.From the data analysis it can be concluded that the majority of high school Civics teacher in Sawahan district City of Surabaya have difficulties in implementing innovative learning strategies.